Integrated lean manufacturing tools and discrete event simulation to examine the improvement in AC split units production line. (25th April 2022) - Alkabaa, Abdulaziz S.
This article applies lean tools of value stream mapping, line balancing, and root cause analysis in the production line of an air conditioner manufacturing plant to improve productivity. The National Institute for Occupational Safety and Health (NIOSH) lifting guidelines and activity charts are applied to assess and improve material handling processes. Discrete event simulation is used to evaluate different scenarios of improvements. Comparisons between existing and improved systems are made using performance criteria such as idle time, production capacity, machine utilisation, and average completion time. The lean tools show significant improvements by increasing the system utilisation from 71% to 87%. The material handling time is reduced by 20%. Activity chart minimises the processing time by 15.6%. Comparing to the existing production processes, the proposed lean tools save 35% of the used resources and maximise the production capacity by 33%, minimise idle time by 65% and reduce average completion time by 38%.